PENETAPAN AWAL RAMADHAN, AWAL SYAWAL, DAN 10 ZULHIJJAH - Efendi, Zul (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2012)
Determination start of ramadan, shawwal and early 10 Zulhijjah State, Saudi Fasting in Ramadan and perform worship to the Holy Land of Mecca Hajji are pillars of Islam, to determine when the fall month of Ramadan and 10 Zulhijjah in Indonesia to implement fasting and praying â€˜Id. This has been a study in this paper. Fasting Ramadan is based on paragraph 183 the second letter. O ye who believe, fasting obligatory upon you, as prescribed for those before you, that ye pious. And implement Eid alÂAdha prayers in Indonesia. To set the start of Ramadan, Shawwal and early 10 Zulhijjah in Indonesia Government in this regard the Ministry of Religious Affairs has been trying to establish at trial Isbatnya, but the Islamic organizations also set according to the will of each, finally khilafiyah always occurs in the initial set and 10 Zulhijjah end of Ramadan. The author believes after reviewing terms of the verses of the Quran, the hadith of the Prophet, and Siwak MUI Fatwa Fiqh that the determination of the government (Kemenag) must be obedient in legal certainty because Islam Indonesia and Indonesia is a unitary state, as also, the Egyptian, Arabia and other countries that set.